Medication error when switching from warfarin to rivaroxaban leading to spontaneous large ecchymosis of the abdominal and chest wall - Flavio Egger; Federica Targa; Ivan Unterholzner; Russell P. Grant; Markus Herrmann; Christian J. Wiedermann (Clinics and Practice, 2016)
Non-vitamin K oral anticoagulant (NOAC) therapy may be inappropriate if prescription was incorrect, the patient’s physiological parameters change, or interacting concomitant medications are erroneously added. The aim of this report was to illustrate inappropriate NOAC prescription in a 78-year-old woman with non-valvular atrial fibrillation and borderline renal dysfunction who was switched from warfarin to rivaroxaban and subsequently developed bruising with hemorrhagic shock and acute on chronic renal failure. Administration of 4-factor prothrombin complex concentrate effectively reversed coagulopathy and stopped bleeding. Retrospective determination of circulating plasma levels of rivaroxaban and warfarin confirmed that excessive anticoagulation was likely due to warfarin that the patient probably continued to take although rivaroxaban was initiated. Pharmacodynamic interaction between rivaroxaban and warfarin may not only be additive but synergistic. In patients at high risk of complications, judicious prescribing and dosing of NOACs, and regular monitoring of concomitant medications and renal function are highly recommended.